MPIA as Solution of Appellate Body Dilemma: An Overview of the Advantages of New Mechanism of WTO Dispute Settlement - Ahmed, Mohamed Salah Adawi; Junxiang, Zhang; Khaled Alsaeed, Basel; Zeeshan Ajmal, Muhammad (International Journal of Scientific Research and Management (IJSRM), 2024)
In December 2019, the WTO Appellate Body, the heart of global trade governance, encountered an unprecedented impasse due to the United States blockade on the appointment of its members. This paper delves into the emergence of the Multi-Party Interim Appeal Arbitration Arrangement (MPIA) as a provisional solution to this deadlock. Established by the European Union and trade partners, and now endorsed by 53 WTO members, the MPIA aims to temporarily fill the void left by the paralyzed Appellate Body by utilizing Article 25 of the DSU. Through a juridical normative methodology complemented by historical and descriptive analysis, this study critically evaluates the MPIA's role within the context of international trade dispute resolution. It compares the MPIA's innovative mechanism against the traditional WTO dispute settlement mechanisms, illuminating both its merits and limitations. The paper argues that while the MPIA represents a creative and necessary stopgap, beyond this, it is not a solution for the challenges facing the WTO's dispute settlement mechanism. The findings emphasize the crucial element for comprehensive reform within the WTO's Dispute Settlement Mechanism (DSM) to regain its functionality and credibility in international trade dispute settlement.